Tinjauan Yuridis Tindakan Pemalsuan dan Pengedaran Vaksin Palsu Menurut Hukum Pidana: Tinjauan Yuridis Tindakan Pemalsuan dan Pengedaran Vaksin Palsu Menurut Hukum Pidana - Hanna Wijaya; Yohanes Firmansyah; Yana Sylvana; Michelle Angelika S (Jurnal Medika Hutama, 2021)
Vaccines are essential things that are used to prevent various infectious diseases. Therefore, the need for vaccines continues to increase from time to time in line with demographic developments. This in itself has caused a criminal loophole related to the circulation of many counterfeit vaccines that are not only circulating in small clinics but also reaching large hospitals. This paper explains the view of criminal law that reviews criminal acts from counterfeit vaccine activities, especially from the point of view of law number 36 of 2009 concerning Health.